Biologia floral e sistema de reprodução de Jacquemontia multiflora (Choisy) Hallier f. (Convolvulaceae) - Piedade-kiill, Lúcia Helena; Ranga, Neusa Taroda [UNESP] (Sociedade Botânica de São Paulo, 2000)
The present study deals with the aspects of phenology, floral biology and reproductive system of Jacquemontia multiflora, a caatinga species at the Fazenda Catalunha, Santa Maria da Boa Vista - PE. The species is an annual liana, with cornucopia pattern of flowering. The peak of flowering occurs between the end of March begining of April at the end of the wet season. Its cymose inflorescences have the main axes elongated, exposing the flowers well out the foliage leaves. The blue flowers are shallow campanulate, scentless and producing a very low quantity of nectar. Anthesis is diurnal, the flowers beggin to open at around 05:30h., are ephemeral, lasting for about nine hours. The most frequent visitors are bees (Apidae and Halictidae). Apis mellifera and Trigona spinipes were considered the main pollinators of this species. J. multifora is facultatively autogamous, producing fruits either after self (30%) and cross (60%) manual pollination.

Aspectos da fenologia, biologia da polinização e reprodução de Jacquemontia multiflora foram estudados na Fazenda Catalunha, Santa Maria da Boa Vista-PE. J. multiflora é uma liana anual, que apresenta floração do tipo cornucópia, com pico desta fenofase no bimestre março/abril, que corresponde ao final da estação chuvosa. As flores estão reunidas em cimeiras que apresentam eixo principal desenvolvido, expondo as flores acima da folhagem. As flores são raso-campanuladas, azuis, inodoras e secretam pequenas quantidades de néctar. A antese é diurna, ocorrendo por volta da 5:30h., e a duração das flores é de aproximadamente nove horas, podendo ser consideradas como efêmeras. Abelhas Apidae e Halictidae são os visitantes mais frequentes. Apis mellifera e Trigona spinipes são consideradas como principais polinizadores desta espécie. Quanto ao sistema de reprodução J. multiflora é autógama facultativa, produzindo frutos e sementes por autopolinização manual (30%) e também por polinização cruzada (60%).
Floral biology and reproductive system of Jacquemontia multiflora (Choisy) Hallier f. (Convolvulaceae)
Keywords: Floral biology; reproductive system; Jacquemontia multiflora